2022
DOI: 10.1371/journal.pone.0268593
|View full text |Cite
|
Sign up to set email alerts
|

Thermal adaptation and fatty acid profiles of bone marrow and muscles in mammals: Implications of a study of caribou (Rangifer tarandus caribou)

Abstract: Mammals have evolved several physiological mechanisms to cope with changes in ambient temperature. Particularly critical among them is the process of keeping the membrane of cells in a fluid phase to prevent metabolic dysfunction. In this paper, we examine variation in the fatty acid composition of bone marrow and muscle tissues in the cold-adapted caribou (Rangifer tarandus caribou) to determine whether there are systematic differences in fatty acid profiles between anatomical regions that could potentially b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In contrast, our study found that PL was the predominant lipid class in spinal cords, followed by sphingolipids and glycerolipids. Morin et al [24] investigated the FA composition of different bone marrows in caribou and found that palmitic acid and oleic acid were present at similar levels (~30%), while stearic acid was present at a level of ~27% in the lumbar marrow. Steiner-Bogdaszewska et al reported an extremely low level (~3%) of stearic acid in the metatarsal bone marrows of red and fallow deer [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study found that PL was the predominant lipid class in spinal cords, followed by sphingolipids and glycerolipids. Morin et al [24] investigated the FA composition of different bone marrows in caribou and found that palmitic acid and oleic acid were present at similar levels (~30%), while stearic acid was present at a level of ~27% in the lumbar marrow. Steiner-Bogdaszewska et al reported an extremely low level (~3%) of stearic acid in the metatarsal bone marrows of red and fallow deer [25].…”
Section: Discussionmentioning
confidence: 99%